Prudent Behavior in the Use of Paylater: The Influence of Digital Financial Literacy, Mental Accounting, Motivation, and Sales Promotion - Alvina Hanazenira; Irni Rahmayani Johan (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2025)
The ease of paylater makes people interested in using paylater to achieve their goals, even though using paylater can also provide risks to the people who use it. This study involved respondents with millennial generation criteria and have used or are using paylater in Indonesia which aims to analyze the effect of digital financial literacy, mental accounting, motivation, and sales promotion on paylater precautionary behavior. Data obtained through online questionnaires using Google Form. The data analysis used descriptive analysis, correlation test, and Structural Equation Modeling (SEM) analysis. he results show that digital financial literacy and mental accounting have significant positive effects on paylater precautionary behavior, while motivation has a significant negative effect. No significant direct effects were found between digital financial literacy and mental accounting, or between sales promotion and paylater precautionary behavior; however, both digital financial literacy and sales promotion indirectly influence paylater precautionary behavior through motivation as a mediating variable. This study recommends financial planning and management training or educational programs to promote long-term financial thinking in paylater use and to reduce impulsive spending behavior